Deletion of the genes waaC, waaF, or waaG in Escherichia coli W3110 disables the flagella biosynthesis. (23rd May 2016) - Wang, Zhou; Wang, Jianli; Ren, Ge; Li, Ye; Wang, Xiaoyuan
Abstract : Flagella assembly was investigated in the Escherichia coli W3110 wild‐type strain and Δ waaF, Δ waaC, and Δ waaG mutant strains that only synthesize lipopolysaccharide with different lengths, using transmission electron microscopy and whole genome transcriptome profiling. Under the electron microscope, the flagella were observed on the cell surface of the W3110 strain but not the Δ waaC, Δ waaF, or Δ waaG strains. Transcriptional profiling showed that 1382 genes in Δ waaC, 526 genes in Δ waaF, and 965genes in Δ waaG were significantly regulated compared to the control W3110 strain. These genes were further analyzed by gene ontology and KEGG pathway. Although there were significant transcriptional differences among the Δ waaC, Δ waaF, and Δ waaG strains, genes related to flagella assembly and bacterial chemotaxis (the linkage between the flagella and the environment) were significantly down‐regulated in all three strains. The data demonstrated that flagella assembly in E. coli depends on the length of lipopolysaccharide.